Student Teacher's Language Ability and Its Effects toward Teaching and Learning Process - Asihlya Sandu (Universitas Pelita Harapan, 2017)
This paper attempts to explain how a student teacher’s language ability influences the process of teaching and learning in the classroom. Data was in the form of sentences taken from written reflections written by a student teacher. The reflections were written during the student teacher's four-month practicum in a school of the Pelita Harapan Foundation. The approach used in this paper is qualitative descriptive in which data was gathered, analyzed and presented using words. The results show that there are 6 forms of language that show the student teacher’s low language ability: phoneme, prefix, insertion, diction, indirect sentence, and repetition. Besides that, the effects of low language ability toward the teaching and learning process is in instruction and as a result, in classroom management.BAHASA INDONESIA ABSTRAK:Tulisan ini bertujuan untuk memaparkan kemampuan berbahasa mahasiswa guru yang mempengaruhi proses belajar mengajar di dalam kelas. Data yang dianalisis berupa kalimat-kalimat yang diambil dari refleksi tertulis mahasiswa guru yang ditulis selama empat bulan praktek mengajar kelas tiga di salah satu sekolah YPPH. Pendekatan yang digunakan dalam tulisan ini adalah kualitatif deskriptif dimana data dikumpulkan, dianalisis serta dipaparkan menggunakan kata-kata. Hasilnya menunjukkan bahwa terdapat enam bentuk bahasa yang menunjukkan rendahnya kemampuan berbahasa mahasiswa guru yaitu fonem, prefiks, sisipan, diksi, kalimat tidak langsung serta pengulangan. Selain itu, pengaruh kemampuan berbahasa yang rendah dapat dilihat pada instruksi mahasiswa guru yang pada akhirnya juga mempengaruhi manajemen kelas.